2007
DOI: 10.1093/sleep/30.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mirtazapine in Obstructive Sleep Apnea Syndrome

Abstract: Daily administration of 4.5 to 15 mg of mirtazapine for 1 week reduces AHI by half in adult patients with OSA. This represents the largest and most consistent drug-treatment effect demonstrated to date in a controlled trial. These findings suggest the therapeutic potential of mixed-profile serotonergic drugs in OSA and provide support for future studies with related formulations. Mirtazapine also is associated with sedation and weight gain-2 negative side effects in patients with OSA. In view of the above, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 32 publications
1
58
2
2
Order By: Relevance
“…[30][31][32] In this study, we found that a single 15-mg dose of MIR caused sedation for up to 60 minutes after administration, which is consistent with previous results that indicate that the dose of MIR is an important factor in its ability to improve sleep. 29 MIR given in low doses at the onset of treatment has been reported to increase sleep duration in patients with major depression, which suggests that the ability of low-dose MIR to promote sleep may be caused by sedation-related side effects.…”
Section: Experiments 1: Effect Of Acute Mir Dosing On Sedationsupporting
confidence: 92%
“…[30][31][32] In this study, we found that a single 15-mg dose of MIR caused sedation for up to 60 minutes after administration, which is consistent with previous results that indicate that the dose of MIR is an important factor in its ability to improve sleep. 29 MIR given in low doses at the onset of treatment has been reported to increase sleep duration in patients with major depression, which suggests that the ability of low-dose MIR to promote sleep may be caused by sedation-related side effects.…”
Section: Experiments 1: Effect Of Acute Mir Dosing On Sedationsupporting
confidence: 92%
“…Trazodone, at least in theory, has the opposite effect on the upper airway musculature because of its central serotoninergic effect, as suggested by VEASEY et al [18]. Other drugs with serotoninergic activity, such as fluoxetine, mirtazapine and paroxetine, have been tested with some success in animals, although only limited success has been reported in humans, potentially due to minimal effects on the arousal threshold [15,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Mirtazapine is an antidepressant that has mixed profile serotonin agonist/antagonist [19]. Carely et al reported on two trials with mirtazapine to treat OSA.…”
Section: Pharmacotherapiesmentioning
confidence: 99%
“…Mirtazapine caused weight gain and lethargy in their trials. Therefore, mirtazapine is not recommended for the treatment of OSA [19,20].…”
Section: Pharmacotherapiesmentioning
confidence: 99%